The novel "Marusia" by V. Shklar as a combination of a biography and a quasi-biography (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
The heroine of the novel by V. Shkliar Marusya appears as a talented military leader, fighting for the independence of Ukraine, despite many obstacles and difficulties to achieve the purpose because of which her father, brothers, village fellows sacrifised their lives. The novel «Marusya» in that part which relates directly the chieftain activities are fully documented, because  it is based on the memoir materials and real facts. Here you can talk about it as a biographical novel. The same story line that connects the main character and Myron Girnyak, is based mostly on fiction and author’s fantasy. You can definitely speak about quasi-biography.
Keywords: documentary; biography; quasi-biography; non-fiction; document; fact